Global Englishes - Baker, Will (Language teacher); Ishikawa, Tomokazu; Jenkins, Jennifer, 1950- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"The global spread of English, with over two billion users of the language, is now well-documented. English functions as a language of education, business, tourism, and intercultural communication in many settings across the world. Global Englishes offers a clear and comprehensive overview of key areas of the topic, encompassing both World Englishes and English as a Lingua Franca within a single volume. This engaging textbook offers readers the opportunity to reflect on key debates as well as develop their own thinking on real-world language practices and problems in light of Global Englishes theory and research. Organised into a three-part Survey, followed by readings from important texts, this is both an introductory textbook, covering key concepts and themes, and a starting point for further study. It is essential reading for students of Global/World Englishes and ELF in applied linguistics, sociolinguistics, English language teaching, and intercultural communication"--
Keywords: English language -- Foreign countries; English language -- English-speaking countries; English language -- Variation -- Foreign countries; English language -- Variation -- English-speaking countries; English language -- Globalization